Festival of Conner, Apayao as Village Tourist Farm Attraction - Alla, Leandro Banan; Arnawa, I Ketut; Adnyana, I Made Dwi; Sukanteri, Ni Putu; Nyoman Raka, I Dewa; Suryana, I Made (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 16 No 2 (2022): Vol 16 No 2 (2022), 2022)
Farm activity has the potential to be developed as a tourist destination, the problem is why it has not developed optimally. This study aims to assess the perception of the Panagbunga Festival in Conner, Apayao. The study is  descriptive method of research. There are 110 respondents in the study. Data was collected through a structured questionnaire. Results revealed that regarding tourism importance, the participants strongly agreed Panagbunga Festival promotes and showcases Conner municipality as the fruit basket of the north. Regarding cultural relevance, the participants who consider themselves fruit lovers strongly agreed that the Panagbunga Festival enhanced local pride in culture. Regarding socio-economic value, the participants strongly agreed that Panagbunga Festival improves the employment and standard of living of the farmers. As to the promotional measures to promote the festival, Television advertising ranks first. It is concluded that the Panagbunga Festival of Conner, Apayao provided the perceived promotion to the increase of fruit production within the municipality and to the realization of its vision to become the fruit basket of the north. So promotion through festivals is very important for developed as a tourist destination